Cold Air and Occupational Stress as Exacerbating Factors in a 46-Year-Old Male with Chronic Bronchial Asthma : A Family-Centered Approach - Rusnianah, Farida; Setijowati, Nanik; Deuina Grishelda, Irma (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Bronchial asthma is a long-term lung disease that makes the airways swell up and changes how air flows. To manage effectively, it is essential to understand the host and environmental factors that aggravate diseases. This case study analyzes the interaction of genetic factors, environmental influences, and psychosocial stressors in a 46-year-old male with a ten-year history of asthma. Mr. I, who is 46 years old, is having a really serious asthma attack that is making him cough and making it hard for him to breathe. The cold air and stress at work often made matters worse for him. His mother and daughter both have asthma, therefore it runs in the family. Recent flare-ups show how hard it is for people with certain environmental and job-related risk factors to keep their asthma under control for a long time, even after being diagnosed and treated. The patient's symptoms show how hard it may be to deal with asthma. Cold air and stress at work are two key things that make it worse. He smokes at work, which makes it more probable that objects in the surroundings may hurt him. Functional Degree 1 means that the patient can take care of himself, but he needs to see a doctor since he is worried about his health and can't sleep well. To enhance his quality of life and avert subsequent flare-ups, it is crucial to implement a family-centered strategy that encompasses educating him on avoiding triggers and complying with both pharmaceutical and non-pharmacological treatments. This instance exemplifies the necessity of identifying and mitigating specific environmental and behavioral triggers in the management of chronic asthma. A personalized treatment strategy and thorough education for patients and their families can considerably improve asthma control and maintain functional independence, especially in cases of chronic illness and severe risk factors.